Impact of dark matter on strange quark stars described by different quark models - Yida Yang; Chen Wu; Ji-Feng Yang (European Physical Journal C: Particles and Fields)
Abstract Dark matter is hypothesized to interact with ordinary matter solely through gravity and may be present in compact objects such as strange quark stars. We treat strange quark stars admixed with dark matter as two-fluid systems to investigate the potential effects of dark matter on strange quark stars. Quark matter is described by the quasiparticle model and the extended MIT bag model for comparison. Dark matter is treated as asymmetric, self-interacting, and composed of massive fermionic particles. The two-fluid Tolman–Oppenheimer–Volkoff (TOV) equations are employed to solve for specific stellar properties. Our analysis yields relations between central energy density and mass, radius and mass, as well as tidal deformability and mass. The calculated curves generally align with observational data. In particular, we find that the pattern in which fermionic asymmetric dark matter affects the properties of strange quark stars may not be influenced by the equation of state (EOS) of strange quark matter.